Taxonomy of freshwater sponges of Maharashtra, India, with illustrated descriptions and notes on ecology and habitats (Porifera: Spongillida: Spongillidae) - Jakhalekar, Shriraj S.; Ghate, Hemant V. (Zootaxa, 2016)
We present additional taxonomic descriptions, with Scanning Electron Microscopy (SEM) illustrations, field observations documented by colour photographs, and notes on habitats and ecology of Corvospongilla ultima (Annandale), Eunapius crassissimus (Annandale), Stratospongilla bombayensis (Carter), S. gravelyi (Annandale) and S. indica (Annandale) from recent sponge collections made in western Maharashtra, India. Stratospongilla gravelyi is rediscovered after a century, and along with it, C. ultima and S. indica are illustrated with SEM images for the first time, unequivocally differentiating these two species. Additional taxonomic, ecological data and illustrations of Corvospongilla lapidosa (Annandale), Dosilia plumosa (Carter), Ephydatia meyeni (Carter), Eunapius carteri (Bowerbank) and Radiospongilla cerebellata (Bowerbank) are also provided to supplement the previously published SEM illustrations. All ten spongillid species treated here were originally described from India and three of them are known to be endemic to the Indian region. Present study is the first re-examination of these Indian spongillid species using SEM, providing greater resolution of their important taxonomic characters and careful documentation of their habitats.